Victimization of Micro, Small, and Medium Enterprises (MSMEs) in Predatory Pricing Practices within Indonesia’s Digital Marketplace - Rully Syahrul Mucharom; Yeti Sumiyati; Mochamad Arifinal (Southeast Asian Journal of Victimology, 2026)
The rapid growth of the digital marketplace in Indonesia creates changes in the business competition structure and at the same time increase the risk of predatory pricing which can harm the existence of MSMEs. This article analyzes the forms of economic victimization which experienced by MSMEs as a result of predatory pricing from big players in digital marketplace and discuss the role of competition law to protect small business players as a victim of the competition practice from the victimology aspect. The rapid growth of the digital marketplace generates the concentration of market powers due to the emergence of new business forms through price subsidies, high discounts and large-scale promotions, causing distortions in the structure of the digital marketplace and decreasing the competitiveness of small businesses. This research uses a normative legal method. The legal materials used in this study were collected through library research and qualitative analysis on the competition practice in the Indonesian digital marketplace as well as price war and massive promotion that conducted by big e-commerce and digital business companies, which resulted in economic loss for Indonesian small business players. The results showed that predatory pricing does not only cause economic loss but also create a structure of dependence of MSMEs to the digital marketplace system. Also, the current Indonesian competition law still more focus on proving monopoly practices and have yet accommodate the regulation to protect victim of unfair business competition. The findings suggest that victimology as a modern model in competition law plays a important role to improving the legal protection for MSMEs as vulnerable victims in the digital marketplace ecosystem.